2019
DOI: 10.3390/jcm8060823
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Effectiveness of Long-Acting Injection and Orally Administered Antipsychotics in Reducing Rehospitalization among Patients with Schizophrenia Receiving Home Care Services

Abstract: The current study explored the differences in the effectiveness of first and second generation long-acting injections and orally administered antipsychotics in reducing the rehospitalization rate among patients with schizophrenia receiving home care services in a medical center in Southern Taiwan. Longitudinal data between 1 January 2006, and 31 December 2015, were collected retrospectively. Patients were classified into three treatment groups: First generation antipsychotic (FGA) long-acting injection (LAI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In addition, most published studies of LAIAs are based on Western populations, 8 , 10 , 11 and cannot be generalized to Asian populations, for whom medication preferences, attitudes, and the potential to experience adverse effects of antipsychotics might differ. The few published observational studies of LAIAs from Asia were either from a single medical center with an unrepresentative sample 12 , 13 , 14 , 15 or used an insurance claims database in which confounders could not be well adjusted for. 16 , 17 , 18 , 19 , 20 In addition, few studies reported data on outcomes other than hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, most published studies of LAIAs are based on Western populations, 8 , 10 , 11 and cannot be generalized to Asian populations, for whom medication preferences, attitudes, and the potential to experience adverse effects of antipsychotics might differ. The few published observational studies of LAIAs from Asia were either from a single medical center with an unrepresentative sample 12 , 13 , 14 , 15 or used an insurance claims database in which confounders could not be well adjusted for. 16 , 17 , 18 , 19 , 20 In addition, few studies reported data on outcomes other than hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] In addition, few studies reported data on outcomes other than hospitalizations. [12][13][14][15][16][17][18] Misclassification of exposure is also a major issue in these studies because both people treated with LAIAs alone and those treated with concurrent LAIAs and oral anticoagulants (OAs) were categorized as LAIAs users and compared with people treated with OAs alone. 18,21 Currently, barriers still exist in the clinical use of LAIAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them indicated certain advantages of treatment with LAI: some showed LAIs reduced relapse and rehospitalization rates from treatment with oral antipsychotic(s) before the introduction of LAIs, 24,25 and others showed that they are as effective as oral antipsychotics in preventing relapse in parallel follow-up cohorts. [26][27][28][29] All the reports included relatively high ratio of patients under poor adherence as the main reason for the LAI introduction (ie, 40%-90%). Thus, patients who could be expected to receive benefits from LAI treatment simply through improved adherence were likely to have dominated these study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the studies done previously 16,17 , we reviewed and abstracted baseline patient data from the medical record of eligible patients (i.e., last/latest recorded data prior to initiation of treatment with paliperidone palmitate) for the following variables: age, sex, place of residence, marital status, duration of illness, medical history, index drug, and date of initiation of treatment. Outcome of treatment was collected through a one-time objective assessment of the patient by a third-party psychiatrist (i.e., not involved in the care of the patient, hereinafter referred to as the "Sub-Investigator") using the Structured Clinical Interview for Symptoms of Remission (SCI-SR), a tool that measures remission based on scores (1=absent, 8=present; a score of <3 in all items maintained over a six-month period indicate remission) on eight items of the Positive and Negative Syndrome Scale 18 .…”
Section: Data Collectionmentioning
confidence: 99%